Synthesis, Spectral and DFT Study and Molecular Docking Investigation of (E)-3-(3-Bromo-4-Methoxyphenyl)-1-(4-(Methylthio) Phenyl)Prop-2-en-1-one - Subha, R.; Ingarsal, N. (Journal of Scientific Research, 2023)
In this study, a new (E)-3-(3-bromo-4-methoxyphenyl)-1-(4-(methylthio)phenyl)prop-2-en-1-one was synthesized by a condensation method. It has been characterized using FT-IR, UV-Vis spectra, and NMR spectra. Furthermore, the title compound was subjected to DFT analysis to observe its molecular structure and vibrational wavenumbers using the B3LYP/6-311G(d,p) approach. The total energy distribution (TED) method was used for complete vibrational analysis. Proton and carbon nuclear magnetic resonance (NMR) chemical shifts of the target compound were calculated theoretically by the gauge independent atomic orbital (GIAO) method and compared with experimental data. For the title molecule, the geometrical parameters provided the best agreement with experimental ones. The HOMO-LUMO energy gap, chemical reactivity parameters, Mulliken atomic charge, and molecular electrostatic potential (MEP) are also studied. The results obtained from the DFT analysis were in good agreement with the experimental data. The synthesized compound was also used in molecular docking studies to understand its biological activity.